2015
DOI: 10.1249/01.mss.0000476618.67747.71
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related Genetic Variants And Their Associations With Physical Activity

Abstract: Background: Meta-analysis of genome-wide association studies identified obesity-related genetic variants. Due to the pleiotropic effects of related phenotypes, we tested six of these obesity-related genetic variants for their association with physical activity: fat mass and obesity-associated (FTO)(rs9939609)T>A, potassium channel tetramerization domain containing (KCTD15) (rs11084753)G>A, melanocortin receptor4 (MC4R)(rs17782313)T>C, neuronal growth regulator 1 (NEGR1)(rs2815752)A>G, SH2B adapter protein 1 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that BMI-associated genetic variants are also associated with PA 71 , 72 . Similarly, we found an overall shared genetic basis for PA (especially accelerometer-based measures) with several obesity-related traits (in the expected negative direction of association), suggesting that genetic risk for obesity coincides with genetic propensity for lower PA.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that BMI-associated genetic variants are also associated with PA 71 , 72 . Similarly, we found an overall shared genetic basis for PA (especially accelerometer-based measures) with several obesity-related traits (in the expected negative direction of association), suggesting that genetic risk for obesity coincides with genetic propensity for lower PA.…”
Section: Discussionmentioning
confidence: 98%
“…In total, variants in nine candidate genes (ACE, CASR, CYP19A, FTO, DRD2, CNR1, LEPR, MC4R, NPC1) were found to be associated with physical activity or sedentary behaviour in more than one study. Variants in or close to MC4R was associated with physical activity in three medium quality studies [34,40,42]; however, the GWAS by De Moor et al [28] and Lin et al [31] did not report an association between physical activity and SNPs in the vicinity of the MC4R gene. Online supplementary 6 shows effect size, standard error and p-value for genetic variants from candidate genes studies associated with accelerometry defined phenotypes reported in GWAS summary statistics [26,27].…”
Section: Candidate Gene Studiesmentioning
confidence: 94%
“…The melanocortin system is composed of arcuate nucleus neurons, which produce pro‐opiomelanocortin (POMC) or agouti‐related peptide (AgRP) and cells that express melanocortin 3 and 4 receptors (MC3R and MC4R) . The melanocortin system receives peripheral influence from leptin produced primarily by adipocytes and ghrelin produced by gastric endocrine cells .…”
Section: Physiological Mechanisms Linking Energy Intake Energy Expenmentioning
confidence: 99%
“…Genetic variations at obesity‐related loci have displayed minor effects on the volume of PA (measured through MET score). Subjects with MC4R (rs17782313) C allele (obesity risk variant) spent 3.5% less MET‐hours/week than those with the TT genotype ( p = 0.02) . Subjects with the TMEM18 obesity risk (T) allele spent 4.1% less MET‐hours/week than those with the CC genotype .…”
Section: Genetics Of Physical Activity and Sedentary Behaviourmentioning
confidence: 99%